2021
DOI: 10.1111/ijcp.14466
|View full text |Cite
|
Sign up to set email alerts
|

Does Covid‐19 in children have a milder course than Influenza?

Abstract: Background In December 2019, a novel type of coronavirus infection emerged in the Wuhan province of China and began to spread rapidly. In this study, we aimed to determine the differences between COVID‐19 disease and Influenza. Methods This retrospective study included 164 children with COVID‐19, as well as 46 children with Influenza. The two groups were compared with respect to clinical and laboratory parameters and the rates of intensive care and mechanical ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Some studies reported lower neutrophils in the COVID-19 pediatric groups, 11 , 16 , 19 like that observed in adulthood. 26 …”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Some studies reported lower neutrophils in the COVID-19 pediatric groups, 11 , 16 , 19 like that observed in adulthood. 26 …”
Section: Discussionmentioning
confidence: 68%
“… 17 , 21 Some studies described lower neutrophil count in the COVID-19 group than in the Influenza group. 11 , 16 , 19 Zhao et al showed higher lymphocyte count in children with COVID-19, 10 while lymphocytopenia was more frequent in children with Influenza. 17 , 19 , 21 …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations